(untitled) (Foro de Educacion, 2014)
The struggle of indigenous peoples for education does not to be reduced a fight for a State school, which legitimates differences among people. One of the errors that multicultural policies and pro-indigenous perspectives have is the believing that asserts that it is necessary to keep ancestral practices and manners in order to be indigenous. This belief does not take into account the strategies of resistances that the native communities have had against to governmental elites during the past centuries. The indigenous fight for education should be understood as defensive response to segmentation and exclusion that have been developed by the patriarchal society, the economy and the Bolivian State. This paper focuses on the creative political and educational praxis that are implemented by indigenous communities. It also shows how governmental elites have implemented political tools in order to reproduce hierarchical practices which come from colonial times. We try to bring comprehension regarding the action of indigenous population in education and their tension with State and its pseudo-modernization projects.